Trace Element Geochemistry of Armenian Obsidian Sourcesand the Provenance of Archaeological Obsidian Artefacts - Meliksetian, Khachatur; Pernicka, Ernst; Badalyan, Ruben; Schifer, Thorsten; Keller, Jörg; Gasparyan, Boris; Jrbashyan, Ruben; Navasardyan, Gevorg; Kunze, René (Austrian Academy of Sciences Press)
Since the mid-1990s we have been involved in the study and analysis of obsidian in Armenia, first only intermittently, then between 2002 and 2006 intensively with several field seasons to collect geological samples from all known obsidian sources in Armenia. Later a few samples from the Chikiani source in Georgia were included. For several reasons, this large dataset was only used as background information for various publications and reports but never published in total. Herewith we present neutron activation analyses of 153 obsidian samples together with detailed information on their geological setting and with some outlook on the distribution of obsidian in the Near East, with an emphasis on periods from the Neolithic to the Bronze Age. It is possible to discriminate all sources based on diagrams of a few geochemically significant trace elements that could be determined with high sensitivity and precision.
Keywords: Archaeology